ANALISIS SWOT UNTUK MENENTUKAN STRATEGI KOMPETITIF PADA HADI SUKIRNO LEATHER WORK & HANDICRAFT - Nurwantoro Nurwantoro; Wawan Budi Setyawan (Politeknik ATK Yogyakarta, 2015)
With increasing global competition, the company is required to always pay attention to the market and compete situation more competitive in determining strategy. Competitive strategy is one way to determine the competitiveness of each strength. Use of an effective SWOT analysis can play an important role in determining the competitive strategy, in order to know the strengths, weaknesses, opportunities and threats faced by enterprise IT in maintaining the viability and continuity of the company. A problem in which you want to find the answer in this study is